1987
DOI: 10.1111/j.1365-2044.1987.tb04050.x
|View full text |Cite
|
Sign up to set email alerts
|

Awareness under anaesthesia due to a defective gas‐loaded regulator

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…A defective fail-safe gas-loaded regulator resulted in oxygen flow through the N 2 O flowmeter. 3 A similar case of leakage of O 2 through N 2 O flow meter due to faulty O 2 fail safe device was also reported. 4 In this case report, ruptured diaphragm and loose packing in oxygen failure safety valve allowed oxygen to flow through N 2 O flow meter ( Figure 2).…”
Section: Discussionmentioning
confidence: 63%
“…A defective fail-safe gas-loaded regulator resulted in oxygen flow through the N 2 O flowmeter. 3 A similar case of leakage of O 2 through N 2 O flow meter due to faulty O 2 fail safe device was also reported. 4 In this case report, ruptured diaphragm and loose packing in oxygen failure safety valve allowed oxygen to flow through N 2 O flow meter ( Figure 2).…”
Section: Discussionmentioning
confidence: 63%
“…A Medline search from 1983 found that no such problems with the Midogas nitrous oxide/oxygen blender have been reported. However there have been two cases of oxygen contaminating the nitrous oxide line due to defects in the O 2 fail-safe device in anaesthetic machines 9,10 . This led to awareness in those individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…. The pipeline is polluted by the`wrong' gas at the point of interconnection or cross-connection of two pipelines [3]. .…”
Section: Introductionmentioning
confidence: 99%